Time-resolved optical emission spectroscopy in CO2 nanosecond pulsed discharges. (19th November 2021) - Ceppelli, M; Salden, T P W; Martini, L M; Dilecce, G; Tosi, P
Abstract: Nanosecond repetitively pulsed discharges at atmospheric pressure have shown comparatively high performances for CO2 reduction to CO and O2 . However, mechanisms of CO2 dissociation in these transient discharges are still a matter of discussion. In the present work, we have used time-resolved optical emission spectroscopy to investigate the CO2 discharge progression from the initial breakdown event to the final post-discharge. We discover a complex temporal structure of the spectrally resolved light, which gives some insights into the underlying electron and chemical kinetics. We could estimate the electron density using the Stark broadening of O and C lines and the electron temperature with C + and C ++ lines. By adding a small amount of nitrogen, we could also monitor the time evolution of the gas temperature using the second positive system bands of N2 . We conclude that the discharge evolves from a breakdown to a spark phase, the latter being characterised by a peak electron density around 10 18  cm −3 and a mean electron temperature around 2 eV. The spark phase offers beneficial conditions for vibrationally enhanced dissociation, which might explain the high CO2 conversion observed in these plasma discharges.